An evaluation of corporate governance practices on board member selection and recruitment in Namibian state owned enterprises. - Kefas, Naomi Natangwe (My University, 2014)
This study highlights the importance of corporate governance in the selection and recruitment of board members in Namibian SOEs. Furthermore, the study intended to investigate the criteria and methods used in the selection of board members and also to examine the corporate governance practice in nomination of board members. Critical analysis and empirical studies were conducted to answer the objectives of the study. The poor performance of the state-owned enterprises is attributed to political interference in the activities of the organisations which include the selection and recruitment of the board of diVice Chancellors. The study followed the positivist approach and a quantitative research design to gather the relevant data from the state-owned enterprises. Self-administered questionnaires were designed, and a sample of 40 senior managers and diVice Chancellors was selected to complete the questionnaires. Thirty-five (35) of the questionnaires were returned which constituted adequate respondents for the research. According to this study it was found, although the board nomination is well qualified with adequate experience, corporate governance guidelines are not being fully adhered to. This study found out that there is a relationship between SOEs overall corporate governance performance and board nomination guidelines. Overall the study found that there is a strong relationship between board nomination and corporate governance performance of state owned enterprises in Namibia. Based on the findings of the study, recommendations were highlighted in order to improve selection and recruitment of board members at the state-owned enterprises. One of the main recommendations is that, there should be proper guidelines to ensure good corporate governance in the selection of board members, and an effective Nomination Committee should be in place. Furthermore, political interference should be minimised or otherwise avoided altogether.
Mini-thesis presented in partial fulfillment of the requirements for the degree of Masters in Leadership and Change Management in the Harold Pupkewitz School of Business, NUST.
Keywords: Corporate governance - Namibia; Corporate practices - Namibia; SOEs - Namibia; State Owned Enterprises - Namibia; Board member selection - SOEs - Namibia; Selection and recruitment - SOEs - Namibia; Master's theses - Namibia; NUST - Master's theses, 2014